2013
DOI: 10.1093/geronb/gbt060
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ethnicity and Gender on Caregiver Health in Older New Zealanders

Abstract: The poorer health of caregivers supports previous findings on the detrimental health effects of caregiving. Caregiving may have more detrimental effects on Māori health outcomes due to existing inequalities in health, barriers to formal support services, and the multiple roles of elder Māori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The majority of the elder group was spouses, while the majority of the non-elder group was sons or daughters. Most previous studies have indicated that women are the major primary family caregivers, especially in caring for the elderly or patients with chronic disease [6], [8], [12]. Currently, the number of females working is increasing; therefore, the caregiving duties for families with chronic disease have few gender differences in the non-elder group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the elder group was spouses, while the majority of the non-elder group was sons or daughters. Most previous studies have indicated that women are the major primary family caregivers, especially in caring for the elderly or patients with chronic disease [6], [8], [12]. Currently, the number of females working is increasing; therefore, the caregiving duties for families with chronic disease have few gender differences in the non-elder group.…”
Section: Discussionmentioning
confidence: 99%
“…The study also demonstrated that caregivers providing higher levels of care and more care across time had poorer health outcomes. Long-term and heavy daily caregiving may have detrimental effects on health status due to a lack of formal support resources and the strain of multiple roles [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is some research literature on caregiving in New Zealand, particularly in relation to caregiver stress, there is little focusing on sex, ethnicity and their interactions in caregiving, especially for those of advanced age. The New Zealand Longitudinal Study of Ageing found that women and Māori provided higher levels of care . That women provide the most care arises from gendered role expectations and, in later life, from their longevity and the fact that their spouses or partners tend to be older…”
Section: Introductionmentioning
confidence: 99%